Effect of long term application of fertilizers on soil nutrient status in groundnut (Arachis hypogaea L): Effect of long term application of fertilizers on soil nutrient status in groundnut (Arachis hypogaea L) - K V NAGA MADHURI,; P RATNA PRASAD,; P V R M. REDDY,; KHALID AHMADY,; M. MADHAN MOHAN, (Journal of Oilseeds Research, 2020)
An experiment was conducted in long term fertilizer experiments (initiated in 1981) plot with groundnut as test crop to study the soil nutrient availability at harvest of groundnut. There were 11 treatments arranged in RBD with four replications. The highest value of available N (87 kg/ha) was recorded in treatment T10 [NPK + lime (100 kg/ha) at flowering]. Depletion of available P was seen in seven treatments when compared with initial P (47.6 P2O5 kg/ha). Available K content of the soil decreased in all the treatments as compared with the initial status (216 K2O kg/ha).